Multi-match Packet Classification on Memory-Logic Trade-off FPGA-based Architecture - Zerbini, Carlos A. (2013)
Fil: Zerbini, Carlos A. Universidad Tecnológica Nacional. Departamento de Ingeniería Electrónica; Argentina.